Integrating behavioural change and gamified incentive modelling for stimulating water saving. (April 2018) - Novak, J.; Melenhorst, M.; Micheel, I.; Pasini, C.; Fraternali, P.; Rizzoli, A.E.
Abstract: Stimulating consumers to save water is a challenge and an opportunity for water demand management. Existing ICT systems for behavioural change often do not consider the underlying behavioural determinants in a systematic way. This paper discusses the design of the behavioural change and incentive model combining smart meter data with consumption visualisation and gamified incentive mechanisms to stimulate water saving. We show how the design of such a system can be related to a holistic behavioural change model and how this systematic mapping can inform the design of an integrated incentive model combining different incentive types (virtual, physical, social). The model is implemented in the SmartH2O system and deployed in two pilots. We present the preliminary results for the Swiss pilot, which indicate reduced water consumption, positive user feedback and overall suitability of the designed incentive model. Highlights: Holistic behavioural change and incentive model for water saving applications. Systematic mapping of incentive mechanisms to phases of behavioural change. User-centred visualisations of smart metered consumption data and saving tips target attitudes towards water saving. Integrated gamified incentive model offers social, virtual and physical rewards. Results of a real-world pilot indicate reduced water consumption and suitability of the designed incentive model.